Exodus of Lebanese doctors in times of crisis: a qualitative study - Nemr, Elie; Moussallem, Marianne; Nemr, Rita; Kosremelli Asmar, Michèle (Frontiers in Health Services, 2023)
Introduction Since 2019, Lebanon is experiencing an unprecedented exodus of doctors, seriously threatening the national health system, which is expected to continue without quick and effective solutions. Therefore, this study aimed to understand the factors that push Lebanese doctors to migrate and the factors that retain others in the country. Additionally, this study aims to propose solutions to preserve an adequate supply of medical care amidst the crisis. Methods Qualitative semi-structured interviews and focus group discussions were conducted using pre-developed guides. Purposive and snowball sampling was adopted to recruit physicians who emigrated and physicians staying in Lebanon. Transcripts of interviews and focus groups were coded using Dedoose software and analyzed through a combination of inductive and deductive approaches. Results Emigration was found to be the result of numerous interconnected factors. The main drivers for emigration were declining income, career problems, reduced quality of care, unhealthy work environment, and the deteriorated political and socio-economic contexts leading to instability and insecurity. As for the retention factors, they included affective attachment and sense of belonging to the professional environment and the country, followed by recognition and valorization at work. Several recommendations were developed to maintain quality of care delivery, including reforms of the health system, development of focused human resource retention strategies based on resource mapping evidence, negotiations with recruiting institutions to endorse the code ethics ending unethical practices draining countries' human resources, provision of financial incentives to doctors, and the recognition and valorization of physicians. Other rapid interventions were suggested, such as short-term medical missions to mitigate shortages in certain specialties, telemedicine, adaptation of recruitment processes to compensate for resources shortages in certain specialties, and adoption of task-shifting approaches to alleviate the workload on overburdened specialists. Discussion The findings of this study shed the light on the different factors influencing migration while framing them in the Lebanese context. These findings and recommendations should inform stakeholders and policy makers about the interventions needed to restore the quality of care. The feasibility and sustainability of most formulated recommendations depend on several factors, with political and socio-economic security and stability being the most crucial ones.